2016
DOI: 10.1126/science.aaf8110
|View full text |Cite
|
Sign up to set email alerts
|

Great apes anticipate that other individuals will act according to false beliefs

Abstract: ( fig. S20), the mechanical properties of the synthetic nacre are still not as good as that of natural nacre (35,36) (Fig. 4, B and C). Due to the larger aspect ratio of the aragonite platelets in the synthetic nacre, the platelets exhibit a "partly pullout" behavior, which leads to lower crack-resistance capability.Because the precipitation of the second phase onto the matrix relies on electrostatic force, CaCO 3 and chitin can be substituted by other precursors with opposite charges to make superior composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
427
4
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 619 publications
(446 citation statements)
references
References 26 publications
10
427
4
5
Order By: Relevance
“…However, a series of recent experiments with chimpanzees shows that at least a basic capacity to represent the knowledge of others is present in apes (Bräuer, Call, & Tomasello, 2007;Call & Tomasello, 2008;Hare et al, 2000), and very recent data based on eyetracking suggests a capacity to represent false beliefs as well (Krupenye et al, 2016). These results indicate that a capacity for first-order ToM was already present in the LCAc.…”
Section: Semantic and Pragmatic Components Of Languagementioning
confidence: 85%
“…However, a series of recent experiments with chimpanzees shows that at least a basic capacity to represent the knowledge of others is present in apes (Bräuer, Call, & Tomasello, 2007;Call & Tomasello, 2008;Hare et al, 2000), and very recent data based on eyetracking suggests a capacity to represent false beliefs as well (Krupenye et al, 2016). These results indicate that a capacity for first-order ToM was already present in the LCAc.…”
Section: Semantic and Pragmatic Components Of Languagementioning
confidence: 85%
“…False-belief understanding requires the ability to recognize that mental states are internal representations rather than direct reflections of reality and thus can be inaccurate. This ability may be uniquely human (e.g., Kaminski, Call, & Tomasello, 2008, but see Krupenye, Kano, Hirata, Call, & Tomasello, 2016) and has been argued to play an important role in many human social behaviors (e.g., Herrmann, Call, Hernández-Lloreda, Hare, & Tomasello, 2007). For instance, recognizing that others' representations of the world may differ from our own helps us communicate more effectively and facilitates cooperation (e.g., Baillargeon et al, 2013).…”
mentioning
confidence: 99%
“…An enduring question in cognitive science concerns the extent to which this theory of mind (ToM) is shared with nonhuman animals [1]. Adapting a seminal eye-tracking paradigm [2], we recently showed that humans' closest ape relatives (bonobos, chimpanzees, and orangutans) can pass a modified false belief test [3]. Specifically, apes looked in anticipation of an actor searching for an object where the actor had last seen it, even though the apes themselves knew that it was no longer there.…”
mentioning
confidence: 99%